PELATIHAN FOTOGRAFI GUNA MENDUKUNG PEMASARAN DIGITAL PRODUK USAHA MIKRO KECIL MENENGAH (UMKM) - Yulia Sariwaty; Veny Purba; Maya Retnasary; Ferdinandus Ngare; Dimas Akhsin Azhar; Rani Rahmayani (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2023)
Micro, small and medium enterprises or better known as UMKM have a sizable contribution to the Indonesian economy, therefore a supporting capacity is needed in developing ways of offering products that have experienced a shift from conventional to digital marketing systems. The photography training for marketers of UMKM products this time aims to provide basic training on photography techniques in obtaining product images that support the delivery of visual messages conveyed when carrying out marketing communications through the digital media they use, both social media and market places. The basic photography skills introduced also deliberately utilize smartphone technology to make it easier for marketers to take product images, edit and make product offers in a short time in one medium. The final achievement of this training is shown by the proportional increase and sharpness of the images produced by the participants, this can be seen through the comparison of the results of the images obtained during the pre-test and post-test.